PELATIHAN PELVIC FLOOR MUSCULE EXERCISE (PFME) PADA LANSIA DALAM MENINGKATKAN FUNGSI DEFEKASI - Veroneka Yosefpa Windahandayani; Lilik Pranata; Keristina Ajul; Aniska Indah Fari (Community Development Journal : Jurnal Pengabdian Masyarakat, 2022)
Elderly is part of the life process that cannot be avoided and will be experienced by every individual. The aging process can cause various problems both physically, biologically, socio-economically and mentally. One of the biological disorders that occur in the elderly is defecation disorders. Defecation is the process of removing waste products from the body. Defecation removes the remains of digestion or also substances that do not undergo the digestive process, these substances are in the form of feces that are excreted through the anus. One of the methods used to improve the function of defecation and micturition is Pelvic Floor Muscule Exercises (PFME). The purpose of community service is to train the elderly to do PFME in order to improve defecation function. Training activities for 6 consecutive days, with 15 elderly living in elderly social institutions. The results of the activity show that the activity can increase defecation even though it is not significant. These results state that Pelvic Floor Muscule Exercises (PFME) activities need to be carried out routinely at social institutions for the elderly to help reduce disorders in elderly defecation.